RETRACTED: Genome-Wide Identification and Expression Analysis of WRKY Gene Family in Capsicum annuum L. - Diao, Wei-Ping; Snyder, John C.; Wang, Shu-Bin; Liu, Jin-Bing; Pan, Bao-Gui; Guo, Guang-Jun; Wei, Ge (Frontiers in Plant Science, 2016)
The WRKY family of transcription factors is one of the most important families of plant transcriptional regulators with members regulating multiple biological processes, especially in regulating defense against biotic and abiotic stresses. However, little information is available about WRKYs in pepper (Capsicum annuum L.). The recent release of completely assembled genome sequences of pepper allowed us to perform a genome-wide investigation for pepper WRKY proteins. In the present study, a total of 71 WRKY genes were identified in the pepper genome. According to structural features of their encoded proteins, the pepper WRKY genes (CaWRKY) were classified into three main groups, with the second group further divided into five subgroups. Genome mapping analysis revealed that CaWRKY were enriched on four chromosomes, especially on chromosome 1, and 15.5% of the family members were tandemly duplicated genes. A phylogenetic tree was constructed depending on WRKY domain’ sequences derived from pepper and Arabidopsis. The expression of 21 selected CaWRKY genes in response to seven different biotic and abiotic stresses (salt, heat shock, drought, Phytophtora capsici, SA, MeJA and ABA) was evaluated by quantitative RT-PCR; Some CaWRKYs were highly expressed and up-regulated by stress treatment. Our results will provide a platform for functional identification and molecular breeding studies of WRKY genes in pepper.